Potential Extract Of Red Algae (Gracilaria verrucosa) from Aceh's Coast Against Streptococcus mutans - Shanti Chimisrina; Ridha Andayani; Afrina Afrina; Febby Yustia Yolanda; Suzanna Sungkar (Universitas Syiah Kuala, 2023)
Dental caries is a disease of hard tooth tissue which is demineralized in hard tissue due to bacterial activity that produce acid. Streptococcus mutans known as the main agent of dental caries. Gracilaria verrucosa red algae is one of many marine products of Aceh's coast which containing antibacterial compounds such as flavonoids, tannins and phenols. The aim of this research is to know the antibacterial potency of red algae extract of Gracilaria verrucosa from Aceh's coast towards Streptococcus mutans by observe Minimum Inhibitory Concentration (MIC) and Minimum Bactericicdal Concentration (MBC).  Maceration method was used to produce extraction of Gracilaria verrucosa with 96% ethanol as solvent. The extract concentration used for this study was 20%, 40%, 60%, 80% and 100%.  The results showed that the growth of S. mutans colonies had started to decrease at concentration of 20% i.e. 995.3 x 104 CFU/ml and the least colony growth occurred at concentration of 100% i.e. 54 x 104 CFU/ml.  The conclusion of this research is Gracilaria verrucosa extract has antibacterial potential against S. mutans with MIC is at concentration of 20% whereas MBC is not found.